Seismic activity associated with the September 1977 deflation of the Krafla central volcano in NE-Iceland - Brandsdottir, Bryndis; Einarsson, Pall (Science Institute, University of Iceland, Reykjavik, IS, 1979)
The September 1977 deflation event in the Krafla caldera was one of a series of such events that has been in progress since December 1975. The operation of portable seismographs in the active region and favorable location of the main seismic activity with respect to the permanent seismograph network in NE-Iceland allow a more detailed study of this deflation event than most of the other events. Continuous volcanic tremor appeared on the local seismographs shortly before 16 h on September 8, 1977. Deflation of the volcano began at the same time. A small basaltic eruption broke out on a 0.9 km long fissure near the northern rim of the caldera at about 18 h. Earthquake activity increased soon after the beginning of the tremor and the first earthquakes were located in the caldera region. The earthquake activity then migrated southwards along the Krafla fault swarm with a speed of about 0.5 m secsup -1, and culminated shortly before midnight with 8 earthquakes larger than magnitude 3 that were located near the Namafjall geothermal area 8 km south of the center of the caldera. Shortly after the earthquake activity migrated into the Namafjall area small amounts of basaltic pumice were erupted through a 1138 m deep drill hole there. Depths of earthquakes were 0-6 km in the northern part of the hypocentral zone and 0-4 in the southern part. The first motion pattern of P-waves suggests dip-slip faulting on steeply dipping fault planes consistent with the extensive normal faulting observed on the surface throughout the epicentral zone. The magnitude-frequency relationship was nonlinear and changed during the earthquake sequence. The seismological data strongly support the interpretation that deflation of the Krafla volcano is associated with horizontal migration of magma from the caldera region and formation of dykes in the Krafla fault swarm.